PSV-13 Evaluating Antibody and Cell-Mediated Immune Response Profiles in Beef Cattle. (7th December 2018) - Husseini, N; Barnes, C; Chik, E; Hodgins, D; Mallard, B
Abstract: Concerns regarding food safety and animal health require more effective alternatives with the potential to improve health and productivity. High Immune Response (HIR™) technology is a patented method to identify animals with inherently more robust, balanced and protective immune responses. This approach has been shown to decrease disease incidence in pigs and dairy cattle by about half. Economic benefits of high immune responder dairy cows are in the range of 240/cow/lactation, including reduced treatment costs. Our research focus is on adapting HIR™ for use in Canadian beef feedlots to decrease economically important diseases such as Bovine Respiratory Disease (BRD). HIR test measures IR to non-replicating test antigens (Ag) to elicit both antibody-mediated IR (AMIR) and cell-mediated IR (CMIR). Results on 170 cows of mixed breeds and 126 of their calves at the university research facility demonstrate that calves as young as 3 weeks of age and mature cattle can be ranked for AMIR and CMIR using the HIR test system. A SAS GLM model was used to evaluate the effects of age of dam, parity, and breed composition (y = mu + age + calf/no-calf + breed + error) on IR rank. Regression analysis was used to examine associations between serum IgG of cows and their calves. Results indicated a slight positive correlation between serum IgG in calves of the same dam (R2 = 0.097) when animals of all parities were evaluated, and a greater association was noted when only heifers were evaluated in their first two parities (R2 = 0.64). However, there was no association between AMIR rank of the dam and serum IgG of the calf. There was slight positive association between CMIR rank of the dam and serum IgG of the calf (R2 = 0.05). More dam-calf pairs will be evaluated in the future.